Role of free radical scavengers in oral malignancies treated with radiotherapy - Kushwaha, Virendra; Sahani, Kamal; Sharma, Varun; Saeed, Shaheen; Barman, Santosh Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Radiotherapy has an important role in treatment of oral cancer, but it causes some deleterious effect on healthy cells. Radiation produces free radicals which cause lipo-peroxidation, alteration of protein, and DNA damage, and eventually cell death. This study is designed to evaluate protective role of antioxidants in oral malignancies treated with radiotherapy. Methods: This study is conducted in patients of oral cancer treated with radiotherapy. Patients were divided into two groups, control (n=7) and test (n=9). Patients in control group treated with radiotherapy alone and in test group were supplemented with oral antioxidants throughout the radiotherapy course. Pre and post radiotherapy levels of MDA, SOD and Glutathione reductase were measured in blood and cancerous tissue in both groups and statistically compared. TNM staging before and after radiotherapy and side effects of radiotherapy were also compared in both groups. Results: On statistical comparison of mean difference values of MDA, SOD & GR of control v/s test group, it was noticed that there was a significant reduction in MDA (p<0.05) and significant increase in GR levels (p<0.05) but non significant increase in SOD levels (p>0.05) in test group in comparison to control group for both blood and tissue levels. TNM status of patients improved significantly after radiotherapy in test group. Comparison of side effects between both groups indicated that there was reduction in side effects in test group after radiotherapy. Conclusion: These findings indicated the protective role of antioxidants against free radicals produced in oral malignancies treated with radiotherapy.